2003
DOI: 10.1016/s0921-4534(03)00738-x
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity theorem in high-temperature superconductors

Abstract: This article is devoted to the problem of the validity of the reciprocity theorem in high-temperature superconductors (HTSC). The violation of the reciprocity theorem in zero external magnetic fields has been studied. Experimental data obtained for two different superconducting materials: BiSrCaCuO and YBaCuO are presented. Results show that the basic form of the reciprocity theorem (without consideration of any additional anisotropy) is not valid near the critical temperature. We assume that the reciprocity t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 23 publications
3
17
0
2
Order By: Relevance
“…Existence of the non-zero transverse resistance in zero magnetic field has been recently observed in different HTS materials [5,6,7,8] [6,7]. While the van der Pauw method has been used in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Existence of the non-zero transverse resistance in zero magnetic field has been recently observed in different HTS materials [5,6,7,8] [6,7]. While the van der Pauw method has been used in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…However they did not see any such behaviour. But the violation of the reciprocity theorem has been recently confirmed [7]. One of the most interesting consequences of broken T and P symmetry is the prediction of the existence of an intrinsic orbital moment leading to the spontaneous appearance of macroscopic magnetization at the superconducting transition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Francavilla et al used for explanation of their results Glazmann model [9] based on the annihilation of vortices and antivortices created by transport current. Recently [10] has been shown that this model is not adequate enough thanks to the vortexantivortex symmetry in this system. However a non zero voltage can be observed when inducer vortices are moving under influence of any force which violate vortex-antivortex symmetry ,for example guiding force.…”
Section: Methodsmentioning
confidence: 96%